Addition of Saccharomyces Eubayanus to Scoby Fermentations Modulates the Chemical and Volatile Compound Profiles in Kombucha - Cubillos-Riffo, F; Mardones-Opazo, W; Quintrel-Poblete, P; Pena-Echeverria, T; Saona-Acuna, L; Urbina, K (Academic Press, 2023)
Kombucha is a fermented beverage derived from a sweetened tea fermentation inoculated with a bacteria-yeast consortium referred to as Symbiotic Culture of Bacteria and Yeast (SCOBY). Different SCOBY cultures can impact the beverage s quality and make the whole process highly variable. Adding Saccharomyces yeast cultures to the fermentation process can avoid stalled fermentations, providing a reproducible beverage. Here, we explored using different Saccharomyces eubayanus strains together with SCOBY in the context of kombucha fermentation. Our results show that yeast x SCOBY co-cultures exhibited a robust fermentation profile, providing ethanol and acetic acid levels ranging from 0,18–1,81 %v/v and 0,35–1,15 g/L, respectively. The kombucha volatile compound profile of co-cultures was unique, where compounds such as Isopentyl acetate where only found in yeast x SCOBY fermentations. Metabarcoding revealed that the SCOBY composition was also dependent on the S. eubayanus genotype, where besides Saccharomyces, amplicon sequence variants belonging to Brettanomyces and Starmerella were detected. These differences concomitated global changes in transcript levels in S. eubayanus related to the metabolism of organic molecules used in kombucha fermentation. This study highlights the potential for exploring different S. eubayanus strains for kombucha fermentation, and the significant yeast genotype effect in the profile differentiation in this process. © 2023 Elsevier Ltd